Нормативно-правове регулювання впровадження та використання цифрових технологій у сфері надання адміністративних послуг - Крикавська, Ірина; Krykavska, Iryna (Видавництво Львівської політехніки, 2020)
Досліджено нормативно-правове регулювання впровадження цифрових технологій у сфері надання адміністративних послуг. Проаналізовано закони та підзаконні нормативно-правові акти, що регулюють використання цифрових технологій у сфері надання послуг. Виявлено проблемні аспекти та перспективні напрямки розвитку системи законодавства.

The article is devoted to the interpretation of the regulation and the introduction of digital technologies in the field of administrative services. The article analyzes the laws and by-laws that regulate the use of digital technologies in the field of administrative services. The problematic aspects of the legislative system development are suggested. The legal regulation of the providing of electronic services and the role of Administrative Service Centers in this process are investigated. The quality of use of the digital technologies providing is one of the most important factors that will affect the effectiveness of change and build public confidence in local governments and public authorities. The article is devoted to perspective directions of work on introduction and use of information and telecommunication technologies in the sphere of administrative services. There is a need in legislative regulation of the functioning and protection of e-identification tools.
Legislative regulation of the implementation and of the use of the digital technologies in the provision of administrative services
Keywords: адміністративна послуга; цифрові технології; оцифрування; administrative service; digital technologies; digitization; 342.9